Injury epidemiology in male professional German football: a long-term comparison between the two highest national leagues - Aust, A.; Ahlgrim, C.; Izadpanah, K.; Deibert, P.; Breitbart, P. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Football injuries pose substantial risks to player health, team performance, and club finances. Although injury prevention is a key priority, most epidemiological studies focus on short-term data from international tournaments or clubs outside Germany. This study aimed to examine the injury epidemiology in German elite men`s football through a long-term analysis of a single club competing in both top national leagues.